Analisis Pengaruh Profitabilitas, Kebijakan Dividen, Kebijakan Hutang, Kepemilikan Manajerial Terhadap Nilai Perusahaan (Study Empiris Pada Perusahaan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2018) - Revita Dwi Putri; Jeni Susyanti; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research was conducted with the aim. 1) To Find out and analyze the effect of profitability on the value of real estate companies. 2) To find out and analyze the effect of dividend policy on the value of real estate companies. 3) To find out and analyze the effect of debt policy on the value of real estate companies. 4) to find out and analyze the effect of manajerial ownership on the value of real estate companies proxied by return on investment, dividend per share, debt to equity ratio, manajerial ownership and price earning ratio as the dependent variable Explanatory Research type research. The data used is secondary data. Obtained by documentation techniques. Namely by searching and collecting data on annual reports obtained from the website. The population used in this research is real estate companies listed on the Indonesia Stock Exchange in the period 2016-2018. The sample selection in that study used a purposive sampling method, based on the criteria obtained by 10 companies. The method used is multiple linear regression analysis with hypothesis testing using WU. That partially the debt policy has a significant positive effect on company value while the profitability ratio of dividend policy and manajerial ownership has no partial effect on the value of the company. Keywords: Profitability, Dividend Policy, Debt Policy, Manajerial Ownership, Company Value